Evaluation of Self-Care Practice and Its Associated Factors in Diabetic Patients - Hafed Idris Zaatout; Fatima Al-Zahra Ben Arous (African Journal of Advanced Pure and Applied Sciences, 2023)
Objective: Since diabetes is a lifelong disorder that has no cure, patients’ lack of participation in the treatment process is one of the reasons for the failure to achieve the desired results in diabetes care. Therefore, the disease involves self-care behaviors by patients throughout their lives. Role of self-care practice is crucial to keep the disease under managed and prevent complications. Methods: A cross-sectional study was conducted in a random sample of 200 diabetic patients in Derna City northeastern of Libya. The data were collected using a structured interviewer-administered questionnaire. The analysis and interpretation of data was in term of descriptive statistics. Chi–square test was used to assess the disease-related characters. Results: The study showed that diabetes is more prevalent in women than in men. The participants were of age 12 to 83 years and the mean age was of 54.58 (± 13.58). The study also showed that 64% of participants had no difficulties in the practice of self-care while 36% did not practice any self-care activities. About 61.50% of participants had health problems and disease complications. The study indicated a significant association between regular self-monitoring of blood sugar, which is one of the most important self-care practices and the onset of disease complications (P < 0.05). About 74% of the participants did not undergo any diabetes education, which justifies the lack of a role for self-care in some of the participants. Conclusion: There is an immense need of dedicated self-care behaviors in multiple domains, including food choices, physical activity, proper medications intake and blood glucose monitoring from the patients. Diabetes education is important but it must be transferred to action or self-care activities to fully benefit the patient.